Supervision of the Distribution of Non-Subsidized Industrial Solar Fuel Oil in Bitung City - Waworundeng, Filly Liandri V.; Masengi, Evi; Mokat, Jetty E. H. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The purpose of this study is to describe, analyze and describe how the supervision of the distribution process of Non-Subsidized Fuel Oil - industrial diesel by channeling agents in Bitung City. The research method uses a qualitative approach. Data collection techniques with interviews, documentation studies and observation. The results showed that the supervision of the distribution of Industrial Solar Non-Subsidized Fuel Oil in Bitung City has not been implemented properly because it was found that there are business actors who have been operating and distributing Industrial Solar Non-Subsidized Fuel Oil from Bitung City to commercial areas within Bitung City and its surroundings without licensing so that the volume and quality of supply cannot be monitored and evaluated. In addition, there are business actors who take care of licensing and reporting later after an inspection by the Investigator appointed by the Downstream Oil and Gas Regulatory Agency.